SUSTAINABILITY INDEX AND MULTI-TRAIT STABILITY-BASED IDENTIFICATIONOF CLIMATE-RESILIENT MAIZE HYBRIDS UNDER MULTI-ENVIRONMENTEVALUATION - D. SRAVANI, D. BHADRU, M.V. NAGESH KUMAR, G. USHARANI, A. SARITHA and B. MALLAIAH (The Journal of Research, PJTSAU, 2026)
Climate variability has emerged as a major challenge to maize production in semi-arid agro-ecosystems, influencinggenotype performance and yield stability across environments. Identification of hybrids combining high productivity with stableperformance is therefore essential for sustainable maize production and climate-resilient agriculture. The present investigationwas conducted during Rabi, 2023–24 at three representative maize-growing locations of Telangana, viz., Maize Research Unit(MRU), ARI, Rajendranagar; Agricultural Research Station, Karimnagar and Agricultural Research Station, Tornala. Thirteenmaize hybrids along with two standard checks were evaluated in a Randomized Block Design with two replications. Observationswere recorded on yield and yield contributing characters. The Sustainability Index (SI) was employed to assess yield stabilityacross environments, while multi-trait stability analysis based on the Ideotype Distance Index (IDI) was used to identify superiorhybrids by integrating grain yield and associated agronomic traits. Considerable variation was observed among the hybrids forsustainability and stability parameters. Hybrid BH 419207 recorded the highest Sustainability Index (94.9%), followed by BH417144 (88.9%) and BH 417177 (82.9%), indicating superior adaptability and resilience to environmental fluctuations. Multi-traitstability analysis further identified BH 419207 (IDI = 0.82), BH 417144 (IDI = 1.14) and BH 417177 (IDI = 1.48) as the mostdesirable hybrids. The combined application of Sustainability Index and multi-trait stability approaches effectively identifiedclimate-resilient hybrids, and BH 419207, BH 417144 and BH 417177 are recommended for wider evaluation and potentialcultivation in Telangana and similar agro-climatic regions.